Research on Construction Technology of Municipal Road and Bridge Asphalt Pavement - Wang, Wenhai; Huang, Ziwei (Journal of Theory and Practice of Management Science, 2023)
At present, in the construction of municipal roads and bridges, asphalt concrete pavement is very common. Asphalt concrete pavement has excellent impermeability and crack resistance, and is not prone to cracks in engineering construction. Moreover, the construction is rapid, highly meeting people's needs for road comfort and convenience. To effectively ensure the construction quality of municipal road and bridge asphalt pavement, it is necessary to accurately and comprehensively grasp the construction technology to ensure the safety of road traffic.